Currículo, educação física e diversidade de gênero - Pereira, Fabio Alves dos Santos (2009)
The purpose of the present work is to give meaning and analyze through theory to teaching experiences based on dance and soccer activities for boys and girls during the initial years of elementary school in a public school. The methodological procedure for the research was the qualitative approach, and the research strategy was the narrative of experiences. The experiences happened during dancing and soccer classes in a state public elementary school in São Paulo involving students from grade 1 up to grade 4. For the theoretical track, we looked up works that show a critical view of that matter, specially the ones related to gender, school, curriculum and Physical Education. We have noticed that nowadays, society is stigmatized by profound inequality mainly caused by the triad of domination exploitation: capitalism, racism and patriarchate. Such inequality is also present in school on a daily basis. Despite the symbiosis it forms, we turn our eyes to highlight gender inequality. We may consider gender as a field for studies that, amongst many other functions, intends to show that a man and a woman are social constructions that are not only different but also unequal. In school, gender discrimination is present in many instances of the curriculum. The school and the curriculum represent the best state ideological apparatus which the dominant class has used to guarantee and perpetuate its domination. Through a series of mechanisms and protected by the ideological shade of neutrality, the school defines the identity of the individuals and shows what is adequate for boys and girls and what could be accepted or rejected through reinforcement and punishment. However, this process starts from the birth of the human being, when society indicates the expected roles for men and women, and anything out of that expectation is considered deviation. Physical Education, for many reasons, is a privileged area to discuss gender discrimination. This school subject, from its creation, has presented two strong characteristics: it has been used by dominant classes to benefit their own aspirations and it has had discriminatory features, as a rule, against women. The women used to be considered weak and physically incapable, so they were not allowed to practice several sports. Today, women are not legally forbidden to practice such sports, but they still suffer violence. Nowadays, many children are being discriminated in Physical Education classes; therefore they are deprived of stimulus just because they are men or women. Based on the theorization we made in class, we noticed that despite some progress, soccer and dance are still gendered activities, but if the teacher acts as an intellectual transformer, using dialogue, awareness and pedagogical intervention, he will be able to provide equal classes for boys and girls and to diminish discrimination. We advocate that the aspects we focused in this study will make it possible to rethink pedagogy concerning gender